PENERAPAN STRATEGI WHO WANTS TO BE A MILIONER UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS X SMA PGRI PEKANBARU - Yasnita '; Muhammad Nor; Syahril ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aimed to find out the improvement of the students motivation learning by applying strategy who wants to be a milioner. This research is a this study is a pre-experiment One Group Pretest-Posttest Design. The subject of this research is students class X at SMA PGRI Pekanbaru, total of 21 students. In this pre-experimental research design the data collection instrument used was a questionnaire of learning motivation of ARCS, where students are given a pretest first motivation questionnaire to see the students initial motivation level, After that given treatment by applying the strategy who wants to be a millionaire, then students are given a final motivation questionnaire. The data were analyzed descriptively to see the improvement of learning motivation. The result of this research, score motivation students increase of 19%. Where the average score of students initial motivation of 2.47 is at a low category, while the average score of final student motivation motivation of 2.94 is in the high category. Therefore, it can be concluded that the implementation of strategy who wants to be a milioner able to improve the motivation of students at SMA PGRI PekanbaruKey Words: Who Wants to be a Milioner, Motivation.